2013
DOI: 10.1021/am400370s
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Electrosynthesis of Poly(xanthurenic acid)-Reduced Graphene Oxide Nanocomposite for Highly Sensitive Impedimetric Detection of DNA

Abstract: A novel and simple synchronous electrochemical synthesis of poly(xanthurenic acid, Xa), electrochemically reduced graphene oxide nanocomposite (PXa-ERGNO), via cyclic voltammetry (CV) was reported, where graphene oxide (GNO) and Xa monomer were adopted as precursors. The resulting PXa-ERGNO nanocomposite was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, CV and electrochemical impedance spectroscopy (EIS). The π-π interactions between the conjugated GNO layers and aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…1, the GNO (Fig. 1A) presented comparatively smooth film with slight wrinkles [40]. After the above GNO/GCE being dipped in 0.1 M Zn(NO 3 …”
Section: Apparatuses and Reagentsmentioning
confidence: 96%
“…1, the GNO (Fig. 1A) presented comparatively smooth film with slight wrinkles [40]. After the above GNO/GCE being dipped in 0.1 M Zn(NO 3 …”
Section: Apparatuses and Reagentsmentioning
confidence: 96%
“…Based on a rGO and poly-(m-aminobenzenesulfonic acid, ABSA) nanocomposite (PABSA-rGO), Yang et al reported a sensitive detection method for the PML/RARA fusion gene sequence. 276 Based on the modifications, probe nucleic acids could be anchored on the functionalized graphene surface, and with the hybridization of target nucleic acids, the [Fe(CN) 6 ] 3À/4À probe can report the impedance changes. Jayakumar et al synthesized a first generation (G1) poly(amidoamine) dendrimer (PAMAM) with a graphene core (G@G1PAMAM), and then immobilized G@G1PAMAM covalently onto a mercaptopropionic acid (MPA) monolayer on a Au electrode.…”
Section: Graphene/nucleic Acid Interface-based Bionanotechnological Amentioning
confidence: 99%
“…The covalent attachment, i.e., the formation of amide bonds between amino-terminated DNA probes and oxygen-containing groups of graphene materials using a carbodiimide, is a well-known procedure and still the predominant procedure [181]. For the covalent procedure, it might be more useful to augment the oxygen functionalities on graphene surfaces by introducing a small molecule such as perylene tetracarboxylic acid [115], poly(xanthurenic acid) [116] and 1-aminopyrene [117]. In this case, both GO and rGO with carboxylic groups serve as a better substrate and surface chemistry can be adopted to increase the number of carboxylic groups required for the covalent attachment of the DNA probe [182].…”
Section: 2mentioning
confidence: 99%
“…The amino group of APTES is crosslinked with the amino group of the biomolecule by glutaraldehyde activation. It is also feasible to increase the oxygen or amino functionalities on graphene surfaces by introducing carboxyl-or amino-containing molecules such as perylene tetracarboxylic acid [115], poly(xanthurenic acid) [116] and 1-aminopyrene [117]. Graphene materials decorated with gold nanoparticles (AuN- Ps) can be conjugated with thiolated biomolecules by exploiting ''well-known AuÀS'' interactions.…”
mentioning
confidence: 99%